Misconception Analysis of Minimum Competency Assessment (AKM) Numeration of High School Students from Field Dependent Cognitive Style - Arian Sah, Retno Wahyu; Nisfi Laila, Alfi Rachma; Setyawati, Astri; Darmayanti, Rani; Nurmalitasari, Dewi (JEMS: Jurnal Edukasi Matematika dan Sains, 2023)
The purpose of this study was to describe the extent of misunderstandings experienced by high school students while tackling Minimum Numerical Ability (AKM) questions modeled on the basis of domain-dependent cognitive styles. The number of students used as subjects in the study was her XI-IPS students in class three (3). The study was conducted at Tawangsari, Tulungagung District, Kedungwal, MA Darul Hikma, Tulungagung District, Jl KH Abu Mansur I. The study was conducted in even-numbered terms of the academic year 2021-2022. A targeted sampling method with the GEFT test (Group Embedded Figure Test) is used to determine research topics and classify students as having subject-dependent cognitive styles or not (subject-dependent). The results showed that students were categorized based on their AKM numbering test response results of low, medium, and high misconceptions. The number of questions is 3 questions. The first item is used to make sure that the indicator cannot repeat the concept. The second item is used to determine that the indicator fails to formulate the concept correctly in various mathematical representations. The index cannot determine the formula that answers the question. Indicators cannot apply formulas or algorithms to solve problems. The third item is used to see indicators of inability to use formulas or problem-solving algorithms. The results obtained show that subject-specific style students with low misunderstandings score higher from responses to AKM numbering questions than students with moderate and high misunderstandings.